2011
DOI: 10.1186/1743-422x-8-370
|View full text |Cite
|
Sign up to set email alerts
|

Is ultra-violet radiation the main force shaping molecular evolution of varicella-zoster virus?

Abstract: BackgroundVaricella (chickenpox) exhibits a characteristic epidemiological pattern which is associated with climate. In general, primary infections in tropical regions are comparatively less frequent among children than in temperate regions. This peculiarity regarding varicella-zoster virus (VZV) infection among certain age groups in tropical regions results in increased susceptibility during adulthood in these regions. Moreover, this disease shows a cyclic behavior in which the number of cases increases signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The incidence and age distribution significantly depart from the typical behavior observed in other tropical regions. 11 Strikingly, the temperature profile and the incidence of varicella in Mexico displayed remarkable similarities. Unexpectedly, higher temperatures were associated with an increase in the number of varicella cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The incidence and age distribution significantly depart from the typical behavior observed in other tropical regions. 11 Strikingly, the temperature profile and the incidence of varicella in Mexico displayed remarkable similarities. Unexpectedly, higher temperatures were associated with an increase in the number of varicella cases.…”
Section: Discussionmentioning
confidence: 93%
“…11 To this pattern in more detail, the varicella incidence from 2002 to 2010 was calculated per month in each state. The analysis showed that the number of cases generally increased in February, reaching a maximum from March to May, and declined rapidly around June (Fig.…”
Section: Tropical Regions Of Mexico Follow the Characteristic Cyclic mentioning
confidence: 99%
“…Therefore, varicella seasonality in Spain seems to be slightly different to the winter-spring pattern usually reported from other temperate regions, although the pattern of infection affecting preschool and school-aged children remains identical [16]. In tropical areas, the winter-spring pattern is also frequent, but peaks in August, for instance, have also been reported in tropical areas of Mexico [11]. These seasonal diversities increase the interest in determining the role of meteorologic factors in chickenpox epidemics.…”
Section: Discussionmentioning
confidence: 92%
“…In general, the factors involved in the seasonality and different epidemiology of varicella infections are not fully understood, but VZV genotypes, climatic factors, and population density have been considered to play a role in the dynamics of disease [7,10,11]. In addition, ultraviolet (UV) radiation has been hypothesized to be involved in the worldwide distribution of VZV genotypes [10], but there is no experimental or epidemiologic confirmation of this hypothesis [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation